Application of CAX system for design and analysis of plastic parts manufactured by injection moulding - Ile Mircheski, Andrzej Łukaszewicz, Roman Trochimczuk and Ryszard Szczebiot (Latvia University of Life Sciences and Technologies Faculty of Engineering, 2019)
The purpose of the paper is to present the design of a new plastic part and injection process simulation. Workflow in virtual modelling and simulations in CAx system was presented on an example of the trolley plastic car for kids. The model of plastic car was designed and simulated to determine injection parameters in SolidWorks environment. Based on 3D model of product the mould tool was created. From the virtual testing the most suitable injection point location, material temperature as well as fill time and required injection pressure have been specified. With these results the designers can avoid the anomalies or defects, in real plastic things with actual injection’s process parameters, like: air traps, weld lines and sink mark. Such analyses allow the designer to develop a proper mould 3D model, to save the mould setup time as well as to reduce cost for manufacturing of mould.
Keywords: injection moulding, mould design, plastic parts, CAx, SolidWorks